Determination and Freedom in Creation Mediated by Sign Systems - Newton Duarte; Efrain Maciel e Silva; Ricardo Eleutério dos Anjos (Revista Brasileira de Estudos da Presença, 2021)
This article examines the relationship between determination and freedom in the human act of creation mediated by the use of sign systems. To this end, an approximation is made between György Lukács’ philosophical-ontological reflection on the dialectic between teleology and causality in work activity and analysis carried out by Lev Vigotski on the importance of sign systems for human psychic development. It is concluded that creation involves complex relations between the freedom of the subjects and the socio-cultural determinations.